2022
DOI: 10.3847/1538-4357/ac7870
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Instability-driven Nanojets in Coronal Loops

Abstract: The recent discovery of nanojets by Antolin et al. represents magnetic reconnection in a braided field, thus clearly identifying reconnection-driven nanoflares. Due to their small scale (500 km in width, 1500 km in length) and short timescales (<15 s), it is unclear how pervasive nanojets are in the solar corona. In this paper, we present Interface Region Imaging Spectrograph and Solar Dynamics Observatory observations of nanojets found in multiple coronal structures, namely, in a coronal loop powered by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
7
12
0
Order By: Relevance
“…In these cases, energy release is likely at smaller spatial scales, which then leads to the formation of blob-like features and rapidly evolving EUV emission from these loops. All these features are also consistent with the interpretation of the recently discovered nanojets (Antolin et al 2021;Sukarmadji et al 2022). While providing evidence for intermittent coronal heating from the relaxation of braided loops, our study identified the operation of both gentle and impulsive modes of energy release through reconnection in the solar corona.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In these cases, energy release is likely at smaller spatial scales, which then leads to the formation of blob-like features and rapidly evolving EUV emission from these loops. All these features are also consistent with the interpretation of the recently discovered nanojets (Antolin et al 2021;Sukarmadji et al 2022). While providing evidence for intermittent coronal heating from the relaxation of braided loops, our study identified the operation of both gentle and impulsive modes of energy release through reconnection in the solar corona.…”
Section: Discussionsupporting
confidence: 89%
“…The authors suggested that nanojets are produced as a result of magnetic reconnection and subsequent relaxation of braided coronal loops. Furthermore, Sukarmadji et al (2022), who observed additional cases of nanojets in magnetic features hosting cooler plasma including coronal rain, suggested that nanojets are a general result of magnetic reconnection and that not only braiding, but also Kelvin-Helmholtz and Rayleigh-Taylor instabilities can cause them. An open question in nanojets is whether they occur in coronal loops that do not show a signature of cool plasma or coronal rain.…”
Section: Introductionmentioning
confidence: 99%
“…From the plots in the left and middle panels it can be seen that these parameters are positively correlated for the outward jets, but negatively correlated for inward jets. We found a similar negative correlation of 45% and 49% was found for speed-length and speed-lifetime for the inward jets listed by Sukarmadji et al (2022). It can be seen in the right panel of the Figure 6 that there is a good correlation of ≈75% between the length and widths of the outward jets.…”
Section: Correlation Between Physical Parameters Of Nanojetssupporting
confidence: 81%
“…However, for the observed sample of inward jets, a negligible correlation was found between the two parameters. A similar, however unreported, strong correlation of ≈82% was found for such jets listed by Sukarmadji et al (2022).…”
Section: Correlation Between Physical Parameters Of Nanojetssupporting
confidence: 69%
See 1 more Smart Citation